Connectors for electrical and electronic equipment. Product requirements. Rectangular connectors. Detail specification for protective housings for use with 8-way shielded and unshielded connectors for industrial environments incorporating the IEC 60603-7 series interface Part 3-106, (8th September 2023) - British Standards Institution,
No abstract available